The definition of neuronopathic Gaucher disease - Schiffmann, Raphael (J Inherit Metab Dis, 2020)
Neuronopathic Gaucher disease (nGD) has a very wide clinical and genotypic spectrum. However, there is no consensus definition of nGD, including no description of how best to diagnostically separate the acute form—Gaucher type 2—from the subacute or chronic form—Gaucher type 3. In this article, we define the various forms of Gaucher disease with particular emphasis on the presence of gaze palsy in all patients with nGD. This consensus definition will help in both clinical diagnosis and appropriate patient recruitment to upcoming clinical trials.